The Relationship Between Dietary Patterns And Menstruation With Anemia Status Of Female Adolescents At State SMAN 1 Ngunut, Kabupaten Tulungagung - Eva Agustina Yalestyarini; Heri Saputro; Suci Anggraeni (Universitas STRADA Indonesia, 2026)
Adolescent girls as puberty age group , often lack of nutrition rich in iron because many of them had restricted food consumption habit. Moreover , the habit of consuming types of snacks that have no nutritional elements rich in iron , was the tendency on the part of young women until they were suffered with anemic . In Indonesia, the prevalence of anemia in adolescent girls in 2006 , was 28 % . Data collected from Survei Kesehatan Rumah Tangga (SKRT) in 2012 stated that the prevalence of deficiency anemia in adolescent girls aged 10-18 years is 57.1 % ( Depkes RI, 2012) . The results of the current survey of iron tablet supplementation program by Dinas Kesehatan Tulungagung in 2013 , showed that SMA Negeri 1 Ngunut was one of the schools that have students with anemia figure quite high, about 31 % . This study aims to determine the relationship of dietary habits and menstrual status of anemia in adolescent girls in SMA Negeri 1 Ngunut Tulungagung. This research used an analytic correlation with a case control study and a quantitative approach . The sample in this study are young women aged 15 to 17 years a number of 58 met the inclusion criteria consisted of 29 female students in the case group and 29 students in the control group . The sampling technique